2018
DOI: 10.1038/lsa.2018.3
|View full text |Cite
|
Sign up to set email alerts
|

Optically sizing single atmospheric particulates with a 10-nm resolution using a strong evanescent field

Abstract: Although an accurate evaluation of the distribution of ultrafine particulate matter in air is of utmost significance to public health, the usually used PM2.5 index fails to provide size distribution information. Here we demonstrate a low-profile and cavity-free size spectrometer for probing fine and ultrafine particulate matter by using the enhanced particle-perturbed scattering in strong optical evanescent fields of a nanofiber array. The unprecedented size resolution reaches 10 nm for detecting single 100-nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…Detection of a single nanoparticle is of enormous importance in early-stage disease diagnosis, explosive materials detection and semiconductor manufacturing. Optical sensors such as nano-waveguide sensors [69][70][71][72], WGM microcavity sensors [73], and PhC microcavity sensors [74,75] have attracted great attention due to high S, low cost and small size, which has been successfully used for single nanoparticle detection. Moreover, the sensitivity and detection limit are the major factors to characterize the performance of optical sensors.…”
Section: Single Nanoparticle Trapping and Detectionmentioning
confidence: 99%
“…Detection of a single nanoparticle is of enormous importance in early-stage disease diagnosis, explosive materials detection and semiconductor manufacturing. Optical sensors such as nano-waveguide sensors [69][70][71][72], WGM microcavity sensors [73], and PhC microcavity sensors [74,75] have attracted great attention due to high S, low cost and small size, which has been successfully used for single nanoparticle detection. Moreover, the sensitivity and detection limit are the major factors to characterize the performance of optical sensors.…”
Section: Single Nanoparticle Trapping and Detectionmentioning
confidence: 99%
“…Therefore, it is confirmed that the stepwise shifting of ~0.1 nm in transmission spectrum is induced by the binding of individual ErbB2 molecules to the microfiber surface. Thus, the as-prepared sensor achieves biomarker detection at the single-molecule level (28,29).…”
Section: Erbb2 Sensingmentioning
confidence: 99%
“…Reprinted from refs. (a), (b), (c), (d), (e), (f), (g), (h), and (i) with permission: CC‐BY 4.0 open access publication (a,g,i); Copyright 2015 and 2017, American Association for the Advancement of Science (b,c,d); Copyright 2001 and 2012, Royal Society of Chemistry (e,f); Copyright 2017, Springer Nature (h).…”
Section: Applications In Field Research and Diagnosticsmentioning
confidence: 99%